The Area Deprivation Index: A novel tool for harmonizable risk assessment in Alzheimer's disease research. Issue 1 (14th June 2020) - Zuelsdorff, Megan; Larson, Jamie L.; Hunt, Jack F. V.; Kim, Alice J.; Koscik, Rebecca L.; Buckingham, William R.; Gleason, Carey E.; Johnson, Sterling C.; Asthana, Sanjay; Rissman, Robert A.; Bendlin, Barbara B.; Kind, Amy J. H.
Abstract: Introduction: Residence in a disadvantaged neighborhood associates with adverse health exposures and outcomes, and may increase risk for cognitive impairment and dementia. Utilization of a publicly available, geocoded disadvantage metric could facilitate efficient integration of social determinants of health into models of cognitive aging. Methods: Using the validated Area Deprivation Index and two cognitive aging cohorts, we quantified Census block‐level poverty, education, housing, and employment characteristics for the neighborhoods of 2119 older adults. We assessed relationships between neighborhood disadvantage and cognitive performance in domains sensitive to age‐related change. Results: Participants in the most disadvantaged neighborhoods (n = 156) were younger, more often female, and less often college‐educated or white than those in less disadvantaged neighborhoods (n = 1963). Disadvantaged neighborhood residence associated with poorer performance on tests of executive function, verbal learning, and memory. Discussion: This geospatial metric of neighborhood disadvantage may be valuable for exploring socially rooted risk mechanisms, and prioritizing high‐risk communities for research recruitment and intervention.